The role of head movement in capoeira’s armada performance - Oliveira , Gabriela Bonifácio da Costa; Bastos , Flávio Henrique; Gemas Neto, Estefan; Serrão , Julio Cerca; Corrêa, Umberto (Revista de Artes Marciales Asiáticas, 2026)
During armada performance, capoeira player breaks the visual coupling with the opponent because of the turning movement. This study investigated if a phenomenon named “head marking” would characterize as a potential strategy for capoeira player deal with such a break in the informational coupling. The head marking refers to the act of, in turning movements, the head being the last part of the body to move, but the first to finish. Forty experienced volunteers, [male (n = 10) and female (n = 10) beginners, and male (n = 10) and female (n = 10) advanced capoeira players], with an average age of 24.0 ±5.0 years took part in this experiment. The head marking was analysed in relation to armada speed (slow and fast), opponent (with and without), attacking leg (preferred and non-preferred) and learning phase (beginner and advanced). The latter classification was based on the cordon graduations of the Brazilian Capoeira Confederation. Head movement time was smaller than armada movement time (758.8 ms vs. 1916.6 ms, respectively, p < 0.01). Head movement occurred within the armada movement, since it involved negative (-330.47 ms) and positive (806.66 ms) average values for the starting and ending of the head movement, respectively. It was observed that the armadas performed with the preferred lower member had greater average value of head movement time than those performed with non-preferred member (740.41 ms vs. 678.72 ms, respectively, p < 0.05). And, when armadas were performed against a virtual opponent, they involved greater head movement time than those performed without a virtual opponent (758.58 ms vs. 669.43 ms, respectively, p < 0.05). The findings of this study suggest that head movement had functioned as a head marking phenomenon as an armada’s critical component, which vary depending on performers’ lateral dominance and presence of an opponent. They also contribute to the comprehension of motor skill functioning and the elucidation of its underlying mechanisms.